COMPUTATIONAL ACCURACY AND ESTIMATION OF SIMULTANEOUS ECONOMETRICS MODELS. - Zellner, A.; Thornber, H. (Econometrica)
The article features the authors' review of their experiences in computing estimates of coefficients appearing in Klein's Model I, a model which has been used as an illustrative example in many works. It discusses the efforts to check out a two- and three-stage least squares Fortran program for the CDC 1604 computer of the University of Wisconsin. The estimates produced by the program were numerically accurate compared to those published by Rothenberg and Leenders. A new set of coefficient estimates were obtained by running the same computer program on the University of Chicago's IBM 7094.